2012
DOI: 10.5424/sjar/2012103-566-11
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of lowland sawah system on soil physicochemical properties and rice yield in Ashanti Region of Ghana

Abstract: Lowland sawah is viewed as a sustainable alternative to traditional rice culture in West Africa. Sawah (a bund-demarcated, puddled, leveled, and water-regulated rice field) has received growing research attention lately, but no data exist yet on the system's long-term agronomic impact. In a clayey inland-valley soil in southern Ghana, 10-year-old sawah plots (OSP), fresh sawah plots (FSP), and non-sawah plots (NSP) were maintained under both ponded and nonponded conditions in 2007. The OSP enhanced soil status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Notably, there was no significant decline in total C and N under Sawah . In this study area, Obalum et al (Obalum, Oppong, et al, ) reported similar results in Sawah plots over a similar period of about a decade. These results together highlight the potential of lowland Sawah systems of West Africa to enhance water retention and hence soil cooling, a phenomenon that controls excessive decomposition of organic matter in tropical soils (Kyuma, ).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Notably, there was no significant decline in total C and N under Sawah . In this study area, Obalum et al (Obalum, Oppong, et al, ) reported similar results in Sawah plots over a similar period of about a decade. These results together highlight the potential of lowland Sawah systems of West Africa to enhance water retention and hence soil cooling, a phenomenon that controls excessive decomposition of organic matter in tropical soils (Kyuma, ).…”
Section: Resultssupporting
confidence: 80%
“…Addition of nitrogenous fertilizer such as urea and ammonium sulphate without liming commonly practiced in the study area has been reported to decrease the pH of some soils of West Africa (Pierre, Meisinger, & Birchett, ). In the present location, Obalum et al (Obalum, Oppong, et al, ) reported decreases in soil pH of Sawah plots over a similar period of about a decade. They attributed the results to severe weathering and leaching associated with high rainfall in the area, citing Issaka et al ().…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The superiority of sawah systems over traditional rice (Oryza sativa L.) culture in West Africa is no longer debatable (Nwite et al, 2008;Obalum et al, 2012;Ofori et al, 2005). Sawah is a term adopted from Indonesia referring to an ecologically engineered lowland rice field, one that is properly demarcated using bunds, puddled, leveled and rowtransplanted to a high-yielding variety and, thereafter, kept under regulated flooding and routine fertilization.…”
Section: Introductionmentioning
confidence: 99%